2010
DOI: 10.1109/led.2009.2038348
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Polycrystalline Silicon TFT on the Structure of a Dopant-Segregated Schottky-Barrier Source/Drain

Abstract: A high-performance polycrystalline silicon (poly-Si) thin-film transistor (TFT) with Schottky-barrier (SB) source/drain (S/D) junctions is proposed. A p-channel operation on the intrinsic nickel (Ni) silicided S/D was successfully realized with the aid of a thin active layer, despite the fact that the Ni silicided material shows a high SB height (SBH) for holes. Furthermore, for n-channel operation, the dopant-segregation technique implemented on the intrinsic Ni silicide was utilized to reduce the effective S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This indicates the source/drain region of SiNW channel was completed transformed to NiSi phase and the Schottky barrier interface between NiSi source/drain and Si NW channel are inherently formed. 23,24 Fig. 2b shows the cross sectional TEM micrograph of SiNW channel, a rectangular shape of SiNW with multi-layer thick of SiO 2 /Si 3 N 4 /SiO 2 /poly-Si gate were clearly verified.…”
Section: Resultsmentioning
confidence: 84%
“…This indicates the source/drain region of SiNW channel was completed transformed to NiSi phase and the Schottky barrier interface between NiSi source/drain and Si NW channel are inherently formed. 23,24 Fig. 2b shows the cross sectional TEM micrograph of SiNW channel, a rectangular shape of SiNW with multi-layer thick of SiO 2 /Si 3 N 4 /SiO 2 /poly-Si gate were clearly verified.…”
Section: Resultsmentioning
confidence: 84%
“…In particular, we have shown that parasitic resistance effects, related to residual damage induced by ion implantation and not annealed by the laser, can severely limit the advantages of downscaling L on the on-current. Recently, formation of NiSi [25] or raised SiGe [26] source-drain contacts have been proposed to reduce the parasitic resistance. Output characteristics are influenced by the kink effect which has a severe impact on the output conductance of short channel TFTs.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than use a midband gap oxide, a Korean group then explored using Pt silicide for the p-devices and Er silicide for the n-devices [191,192], demonstrating high on/off ratios and low leakages, but at the cost of temperatures up to 500 °C. The use of Ni silicide and dopant segregation was used to realize devices down to channel lengths of 0.1 μm with fabrication temperatures of 400 °C [193]. Most recently, SBTFTs with processing temperatures down to 350 °C, suitable for polymeric substrates using Cr and Ti barriers but only exhibiting on/off ratios of 5 × 10 3 [194].…”
Section: Opportunities Of Sb Devices For Ubiquitous Electronicsmentioning
confidence: 99%